Pengaruh penambahan gum arab dan suhu penyimpanan terhadap kestabilan gel lidah buaya sebagai bahan edible coating [The effect of gum arabic addition and storage temperature on the stability of aloe vera gel as an edible coating] - Ni Made Defy Janurianti; I Made Supartha Utama; Ida Bagus Wayan Gunam (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2022)
Aloe vera gel is a polysaccharide widely used as an edible coating because it contains glucomannan and lignin compounds that can inhibit respiration and transpiration in fruit. However, aloe vera gel has weakness such as easy to change its color, odor, and viscosity. Therefore, a stabilizer is needed, one of which is gum arabic. Storage temperature also affects the stability of aloe vera gel. The purpose of this study was to determine the concentration of gum arabic and the optimal storage temperature in stabilizing aloe vera gel as an edible coating. The study used a completely randomized design (CRD) with a factorial pattern. Parameters tested were viscosity, pH, color change, and sedimentation percentage. The results showed that the optimal concentration of gum arabic to produce stable aloe vera gel was 2% in cold storage (5 ± 1ºC), with stability up to 9 days of storage, on the condition that aloe vera gel has a pH of 4.58 ± 0.04, viscosity 40.67 ± 0.58 m.Pa.s, sedimentation percentage 8.13 ± 14.08% and color change (∆E) during storage 20, 09 ± 0.58. Aloe vera gel added with 2% arabic gum can be an edible coating on fruit or vegetables.